Fecal shedding and transmission of vaccine–derived poliovirus: A systematic review and meta–analysis - Gangerdiwala Mariya Yunus; Kanchwala Aliasgar Taher; Khan Adnan Akram; Dudhane Suraj Anil; Haji Sana Anis; Abusufiyan Shaikh (​​​One Health Bulletin)
Objective: This review aims to summarize the emergence and transmission of vaccine-derived poliovirus (VDPV) across various geographies, its impacts, and the developments of immunization techniques and vaccines. Methods: This systematic review and meta-analysis followed Prioritization of Reporting Items for Systematic Reviews and MetaAnalyses (PRIMSA) criteria and was registered with Prospective Systematic Reviews (CRD42023389248). We included clinical studies such as randomized controlled trials, cohort studies, case reports and cross-sectional studies accessing the fecal excretion of VDPV. Five independent reviewers selected appropriate and relevant studies from PubMed, ScienceDirect and Google Scholar published before January 2023. Statistical analyses were performed using odds ratios (OR) with 95% confidence intervals (Cl) and a random effects model to address heterogeneity (I2), with publication bias evaluated via funnel plots and statistical tests. Results: Out of the 83 initially identified studies, 9 were included in meta-analysis. Participants who received the first dose of monovalent oral polio vaccine (mOPV) did not show statistically significant fecal shedding compared to those treated with the second dose (OR: 1.02, 95% CI: 0.51-2.03, P=0.47). Individuals who received the novel oral polio vaccine (nOPV) significantly reduce virus fecal shedding after the second dose compared to the first dose (OR: 2.95. 95% CI: 1.39-6.25, P=0.00). Sero-conversion rates do not differ significantly between two doses in participants received mOPV (OR:1.10, 95% CI: 0.60-2.01, P=0.35), meanwhile nOPV exhibit a higher seroconversion rate (OR: 0.07, 95% CI: 0.01-0.67, P=0.01). Conclusions: This study provides the evidence supporting the clinical efficacy and safety of nOPV compared to mOPV.